IMPLEMENTING MULTICULTURAL EDUCATIONAL VALUES IN OVERCOMING GROUP FANATISM - Ida Zahara Adibah (PROCEEDING AL GHAZALI International Conference, 2023)
Humans were created by God with differences in religion and equality. The reality in life is that humans are not yet aware of their essence as creatures that have been created differently by God. More and more conflicts are emerging and resulting in bloodshed between people whose motives are not understood. This qualitative research aims to explain the results of instilling multicultural education values ​​that have been carried out by Islamic religious education teachers at Semarang Regency Vocational Schools. This research uses data collection techniques in the form of observation and interviews. Responding to issues regarding conflicts that occur and are often carried out by young people, PAI teachers prove that multicultural education in Semarang Regency can get good results and change the way students think, thereby creating students who understand and can adapt to the school environment. and multicultural society. With these findings, basically education plays an important role in creating change for students, because teachers are able to become role models that their students will definitely follow.